2015
DOI: 10.1155/2015/797862
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Blood Ammonia Level Is a Potential Biological Risk Factor of Behavioral Disorders in Prisoners

Abstract: Hydrothion (H2S) and ammonia (NH3) can be toxic for the human central nervous system and cause psychological disturbances and behavioral disorders. In order to evaluate the association between the two potential toxicants and mental health, in this study, we compare a male prisoner and control population. Forty-nine male prisoners and 52 control volunteers took part in the study. An aggressive behavior assessment, the Self-Rating Depression Scale (SDS), and the State-Trait Anxiety Inventory (STAI) were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Fat-soluble ammonia can enter the brain through the blood-brain barrier and can be used with glutamic acid to synthesize glutamine, leading to a decrease in the excitatory neurotransmitter. This pathway is thought to be a potential mediator for psychiatric disorders such as depression (Duan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Fat-soluble ammonia can enter the brain through the blood-brain barrier and can be used with glutamic acid to synthesize glutamine, leading to a decrease in the excitatory neurotransmitter. This pathway is thought to be a potential mediator for psychiatric disorders such as depression (Duan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic restraint stress aggravated the depressive-like symptoms, and Lactobacillus helveticus NS8 supplementation presented the opposite effect with stress; it also alleviated the behavioral, biochemical, and microbiota aberrations as in the case of the acquired depression model. The lab further found that aggressive behavior was connected with the microbiota; for example, prisoners with violent tendencies presented higher levels of blood ammonia (NH 3 ) ( Duan et al, 2015 ). They also found that ASD, ADHD, and Tourette syndrome were all closely related with gut microbiota abnormalities and could be improved by specific probiotic intervention.…”
Section: Gut Microbiota Gut-brain and Gut-brain Psychologymentioning
confidence: 99%
“…Moreover, plasma ammonia and BAs were increased along with dysregulations of ammonia by-products (i.e., urea) and amino acids (i.e., arginine, glutamate) involved in ammonia production. Herein, we found increased ammonia levels, a known potent neurotoxin found to induce psychological and behavioral disturbances at preclinical and clinical levels [ 36 , 37 ]. In cases of liver damage, as with the steatohepatitis present in WD-fed mice, ammonia could build up in the blood, reach the brain, and impair brain functioning [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%